Extensive Fermi‐Level Engineering for Graphene through the Interaction with Aluminum Nitrides and Oxides. Issue 2 (9th October 2019) - Sciuto, Alberto; La Magna, Antonino; Angilella, Giuseppe G. N.; Pucci, Renato; Greco, Giuseppe; Roccaforte, Fabrizio; Giannazzo, Filippo; Deretzis, Ioannis
Abstract : Despite its structural and chemical stability, graphene is often subjected to n‐ or p‐type doping when interacting with substrates, gate oxides, or environmental molecules. Such interaction shifts the Fermi level of the system away from the Dirac point and alters the intrinsic electronic and transport characteristics of the graphene sheet. The density functional theory is used herein to show that the Fermi level of a graphene/AlN or graphene/Al2 O3 heterostructure can be extensively tuned through the polarity and surface reconstruction of either the nitride or the oxide layer. Hence, Fermi‐level engineering through the manipulation of confining materials can become a viable route for enhancing the selectivity and optimizing the properties of graphene‐based devices. Abstract : Through density functional theory calculations, it is shown herein that the Fermi level of a graphene sheet can be widely tuned from the interaction with AlN and Al2 O3 surfaces of different polarities and reconstructions.